Old ship of Zion : the Afro-Baptist ritual in the African diaspora - Pitts, Walter F., 1947-1991 (Religion in America series (Oxford University Press), 1993)
"'I love the Lord, He heard my cry, ' Deacon cries out as the newly gathered congregation, now seated in their pews, echoes his words in a plaintive tune." Thus begins the Devotional at St. John Progressive Baptist Church, one of many Afro-Baptist services that Walter Pitts observed in the dual role of anthropologist and church pianist. Based on extensive fieldwork in black Baptist churches in rural Texas, this is a major new study of the African origins of African-American forms of worship. Over a period of five years, Pitts, a scholar of anthropology and linguistics, played the piano at and recorded numerous worship services. Offering an extensive history of Afro-Baptist religion in the American South, he compares the ritual structures he observed with those of traditional African worship and other religious rituals of African origin in the New World. Through these historical comparisons, coupled with sociolinguistic analysis, Pitts uncovers striking parallels between Afro-Baptist services and the rituals of Western and Central Africa, as well as African-derived rituals in the United States Sea Islands, the Caribbean, and Brazil. Pitts demonstrates that African and African-American worship share an underlying binary structure: the somber melancholy of the first ritual frame and the joyful, ecstatic trance of the second frame, both essential to the fulfillment of that structure. Of particular interest is his discovery of the way in which the deliberate heightening and strategic suppression of "black English" contribute to this binary structure of worship. This highly original study, with a foreword by Vincent Wimbush, creates a memorable portrait of this vital, yet misunderstood aspect of African-American culture. A model for the investigation of African retentions in the diaspora, Old Ship of Zion will be of keen interest to students and scholars of cultural anthropology, religious studies, and African-American studies, as well as those concerned with the culture of the diaspora, the investigation of syncretism, folklore, and ethnomusicology